Employment relations and ethnic minority enterprise an ethnography of Chinese restaurants in the UK - Li, Xisi (Routledge focus on business and management, 2021)
This book is the first piece of extensive research in studying employment relations in ethnic Chinese small businesses in Britain. It contributes to existing knowledge in three respects. Empirically, it examines the nature of employment relations in the ethnic Chinese restaurant sector in the UK context, a hitherto under-explored area. The study adds new knowledge to the study of employment relations in ethnic minority small firms. Theoretically, it draws out the concept of ethnic twist', which denotes how the conflict between different group members from the same ethnicity shapes patterns of shop floor behaviours, revealing the heterogeneity of people from the same ethnic origins. Methodologically, the research demonstrates the continued importance of the ethnographic approach in studying workplace relations. Additionally, we see lots of literature discussing overseas Chinese businesses in terms of cultural resources, business development, level of integration and structural constraints. Surprisingly little is published on interpretations of small firm workplace relations. This book might illuminate future studies to explore management practices and employment relationships in ethnic Chinese small businesses in different national environments and industry sectors. It will be of interest to researchers, academics and students in the fields of employment relations, human resource management and organisational behavior